2020
DOI: 10.1080/02656736.2020.1788174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warm environment on the skin blood flow response to food intake

Abstract: Background and objective: Warm exposure places high demands on thermoregulation mechanisms, which depend on the effectiveness of the microvascular function. The associations between the microcirculation and metabolism in warm environments have received little attention. The purpose of this study was to explore skin blood flow (SkBF) in response to food intake in a warm environment compared to control. Methods: Thirty-two healthy, acclimated-to-warm-environment and physically active participants were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Moreover, the decrease in cerebral blood flow during hyperthermia [96] may also reduce the impact of hormones. One recent study [97] reported interactions between skin blood flow, food intake, and ambient temperature. This hypothesis may, therefore, be worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the decrease in cerebral blood flow during hyperthermia [96] may also reduce the impact of hormones. One recent study [97] reported interactions between skin blood flow, food intake, and ambient temperature. This hypothesis may, therefore, be worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%